2013
DOI: 10.1107/s0907444912047828
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the ARE-binding domains of Hu antigen R (HuR) undergoes conformational changes during RNA binding

Abstract: Human RNA-binding protein (HuR), a ubiquitously expressed member of the Hu protein family, plays an important role in mRNA degradation and has been implicated as a key post-transcriptional regulator. HuR contains three RNA-recognition motif (RRM) domains. The two N-terminal tandem RRM domains can selectively bind AU-rich elements (AREs), while the third RRM domain (RRM3) contributes to interactions with the poly-A tail of target mRNA and other ligands. Here, the X-ray structure of two methylated tandem RRM dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
142
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(154 citation statements)
references
References 28 publications
11
142
0
1
Order By: Relevance
“…Although RRM1 is the primary ARE recognition domain within HuR, the conformational change that takes place upon RNA binding leads to additional interactions between RRM2 and the target mRNA, ultimately increasing RNA binding affinity (11). This structure, along with other studies investigating the structural basis of HuR/RNA interactions (62), reveals a number of key residues that are predicted to be important for high affinity RNA binding by HuR (11,62).…”
Section: Pdcd4 Mrna Is Bound and Regulated By Hur In Mcf-7 Breastmentioning
confidence: 82%
See 1 more Smart Citation
“…Although RRM1 is the primary ARE recognition domain within HuR, the conformational change that takes place upon RNA binding leads to additional interactions between RRM2 and the target mRNA, ultimately increasing RNA binding affinity (11). This structure, along with other studies investigating the structural basis of HuR/RNA interactions (62), reveals a number of key residues that are predicted to be important for high affinity RNA binding by HuR (11,62).…”
Section: Pdcd4 Mrna Is Bound and Regulated By Hur In Mcf-7 Breastmentioning
confidence: 82%
“…Two N-terminal RNA recognition motifs (RRMs) within HuR mediate recognition of AREs located primarily within the 3ЈUTR of target mRNA transcripts (11,12). A third RRM in the C terminus of HuR has affinity for polyadenosine RNA and is thought to bind to the poly(A) tail of target mRNAs (13,14).…”
mentioning
confidence: 99%
“…While most of the tandem RRMs are separated by a flexible interdomain linker and therefore do not interact in the free state, such as sex-lethal (Sxl), Nucleolin, PTB RRM12, Hrp1, Npl3, and HuR (Crowder et al 1999;Allain et al 2000;Perez-Canadillas 2006;Vitali et al 2006;Skrisovska and Allain 2008;Wang et al 2013), only a few tandem RRMs show interactions; namely, PTB RRM34, Prp24, FIR, and, more recently U2AF65, hnRNPA1, and hnRNPL (Vitali et al 2006;Bae et al 2007;Cukier et al 2010;Mackereth et al 2011;Barraud and Allain 2013;Zhang et al 2013). Such fixed orientation of two RRMs relative to each other often has a direct implication in the mechanism of action of the proteins.…”
Section: Novel Features In Cpeb Rrms: Interdomain Interactions and Exmentioning
confidence: 99%
“…These RRMs are present as a single module in RBM38 35 or as a bipartite module in ELAVL1, where 2 tandem N-terminal domains (RRM1 and RRM2) selectively bind ARE, while RRM3 interacts with the poly(A) tail and other proteins. 36 Furthermore, when the ORF inserts of tested clones were sequenced, we observed that these inserts faithfully represented the predicted RNA-binding domains (Fig. 4B).…”
Section: Rescue and Validation Of Are-interacting Domains In Vitromentioning
confidence: 99%